In the twenty-sixth year of the "republic" of India. - New India Coalition:::Creator::::::::::::
Protest poster calling on viewers to join a demonstration in front of the Indian Consulate in San Francisco to demand revocation of the state of "National Emergency" and the release of political prisoners.